Genetic Pathways of Aging and Their Relevance in the Dog as a Natural Model of Human Aging - Sándor, Sára; Kubinyi, Enikő (Frontiers in Genetics, 2019)
Aging research has experienced a burst scientific efforts in the last decades as the growing ratio of elderly people has begun to pose an increased burden on the healthcare and pension systems of developed countries. Although many breakthroughs have been reported in understanding the cellular mechanisms of aging, the intrinsic and extrinsic factors that contribute to senescence on higher biological levels are still barely understood. The dog, Canis familiaris, has already served as a valuable model of human physiology and disease. The possible role the dog could play in aging research is still an open question, although utilization of dogs may hold great promises as they naturally develop age-related cognitive decline, with behavioral and histological characteristics very similar to that of humans. In this regard, family dogs may possess unmatched potentials as models for investigations on the complex interactions between environmental, behavioral and genetic factors that determine the course of aging. In this review we summarize the known genetic pathways in aging and their relevance in dogs, putting emphasis on the yet barely described nature of certain aging pathways in canines. Reasons for highlighting the dog as a future aging and gerontology model are also discussed, ranging from its unique evolutionary path shared with humans, its social skills and the fact that family dogs live together with their owners, and are being exposed to the same environmental effects.